2023
DOI: 10.1080/16549716.2023.2207862
|View full text |Cite
|
Sign up to set email alerts
|

Association between delayed cesarean section and severe maternal and adverse newborn outcomes in the Somaliland context: a cohort study in a national referral hospital

Abstract: Background In a critical obstetric situation, the time interval between the decision of performing a caesarean section (CS) and delivery can influence maternal and newborn outcomes. In Somaliland, consent for surgical procedures, such as CS needs to be sought from family members. Objective To determine the association between a delay in performing a CS and severe maternal and newborn outcomes in a national referral hospital in Somaliland. The type of barriers leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…This study also showed that DDI was associated with adverse perinatal (increased SCBU admissions and foetal and neonatal deaths). Similar studies conducted in Nigeria [6.7], Somaliland [22] and Uganda [23], also showed increased deaths due to delayed DDI. The poor perinatal outcomes in this study are not unexpected considering the fact that factors such as prolonged labour due to delayed DDI may lead to perinatal asphyxia and increased risk for neonatal sepsis, with subsequent negative impact on the health of the foetus and newborn after birth.…”
Section: Discussionsupporting
confidence: 66%
“…This study also showed that DDI was associated with adverse perinatal (increased SCBU admissions and foetal and neonatal deaths). Similar studies conducted in Nigeria [6.7], Somaliland [22] and Uganda [23], also showed increased deaths due to delayed DDI. The poor perinatal outcomes in this study are not unexpected considering the fact that factors such as prolonged labour due to delayed DDI may lead to perinatal asphyxia and increased risk for neonatal sepsis, with subsequent negative impact on the health of the foetus and newborn after birth.…”
Section: Discussionsupporting
confidence: 66%